Associations of complete blood cell count-derived inflammatory biomarkers with asthma and mortality in adults: a population-based study - Ke, Junhua; Qiu, Fushan; Fan, Wenxi; Wei, Songqing (Frontiers in Immunology, 2023)
Objective This study aims to assess the associations of complete blood cell count (CBC)-derived inflammatory biomarkers with the prevalence of asthma and mortality. Methods Data was collected from the 1999-2018 National Health and Nutrition Examination Survey (NHANES). Mortality was identified using the National Death Index until December 31, 2019. The study analyzed the relationship between CBC-derived inflammatory biomarkers, including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), systemic inflammatory response index (SIRI), and systemic immune-inflammation index (SII), and the prevalence of asthma using multiple logistic regressions. To assess the significance of CBC-derived inflammatory biomarkers in predicting all-cause and respiratory disease mortality in asthma patients, Cox proportional regressions and the random survival forest (RSF) analysis were utilized. Results A total of 48,305 participants were included, with a mean age of 47.27 ± 0.18 years and 49.44% male. Among them, 6,403 participants had asthma, with a prevalence of 13.28%. The all-cause and respiratory disease deaths at a median follow-up of 8.2 (4.5, 12.8) years were 929 and 137 respectively. After adjusting for confounders, the prevalence of asthma was found to be positively associated with NLR, PLR, MLR, SIRI and SII. Compared to the lowest quartile, the highest quartile of NLR (HR=1.765 [1.378-2.262]), MLR (HR=1.717 [1.316-2.241]), SIRI (HR=1.796 [1.353-2.383]) and SII (HR=1.432 [1.141-1.797]) were associated with an increased risk of all-cause mortality. These associations were more pronounced in respiratory disease mortality of asthma patients. RSF analysis showed that MLR had the highest predictive value for all-cause and respiratory disease mortality in adults with asthma. The sensitivity analysis demonstrated the stability of our results. Conclusion The findings suggest that CBC-derived inflammatory biomarkers are associated with a higher risk of all-cause and respiratory disease mortality in adults with asthma.